Serum Potassium Is Positively Associated With Stroke and Mortality in the Large, Population-Based Malmö Preventive Project Cohort. Issue 11 (November 2017) - Johnson, Linda S.; Mattsson, Nick; Sajadieh, Ahmad; Wollmer, Per; Söderholm, Martin
Abstract : Background and Purpose—: Low serum potassium is associated with stroke in populations with cardiovascular disease, hypertension, and diabetes mellitus but has not been studied in a mainly healthy population. We aimed to study the relation between serum potassium and incident stroke and mortality in the Malmö Preventive Project, a large cohort with screening in early mid-life and follow-up >25 years. Methods—: Serum potassium measurements and covariates were available in 21 353 individuals (79% men, mean age 44 years). Mean follow-up time was 26.9 years for stroke analyses and 29.3 years for mortality analyses. There were 2061 incident stroke events and 8709 deaths. Cox regression analyses adjusted for multiple stroke risk factors (age, sex, height, weight, systolic blood pressure, fasting blood glucose, serum sodium, current smoking, prevalent diabetes mellitus, prevalent coronary artery disease, and treatment for hypertension) were fitted. Results—: There was an independent, linear association between serum potassium, per mmol/L increase, and both stroke (hazard ratio, 1.33; 95% confidence interval, 1.17–1.52; P <0.0001) and mortality (hazard ratio, 1.20; 95% confidence interval, 1.13–1.28; P <0.0001). This was significant in subjects both older and younger than the median age (46.5 years), and there was evidence of an interaction with serum sodium. The association was positive and significant for both ischemic stroke and intracerebral hemorrhage and in both hypertensive and normotensive subjects. Conclusions—: Serum potassium, measured in early mid-life, was linearly associated with both incidence of ischemic stroke and intracerebral hemorrhage and all-cause mortality. An interaction with serum sodium implies that factors related to electrolyte balance and incident hypertension may be mediating factors.